CONTRIBUTION OF INFORMAL STREET VENDORS TO LOCAL GOVERNMENT REVENUE DURING POST-COVID 19 PANDEMIC (Journal of Governance and Development (JGD), 2024)
This paper discusses the contribution of informal street vendors to local government revenue generation during the COVID-19 pandemic. Informal street vendors usually develop businesses to sell something and earn an income. They not only generate their income but also generate revenue for the local government. The main objective of local governments is to maintain and improve their efficiency. Therefore, this study aims to understand how informal street vendors contribute to the revenue of Kubang Pasu municipal in the short term, especially after the COVID-19 pandemic. The study covers 50 street vendors in Kubang Pasu. The results of the study show that there are only two (2) independent variables that affect the dependent variable. First, the relationship between affordable licenses and Kubang Pasu Municipal’s revenue shows a positive (0.301) and significant (0.019) relationship at a 0.050 level of significance, which means that the more affordable licenses issued, the higher the Kubang Pasu municipal revenue. Second, the relationship between the current post-pandemic business situation and Kubang Pasu municipal’s revenue shows a positive (0.541) and significant (0.058) relationship at the 0.10 level of significance, which means that the more accessible the business situation is in the post-pandemic period, the higher Kubang Pasu Municipal’s revenue will be. The newly developed revenue source will secure local government revenues in the long term and avoid budget deficits. Kubang Pasu Municipal needs to create new revenue sources, as they are still among the local governments with low revenue sources compared to local governments in other states.